2016
DOI: 10.4314/wsa.v42i3.08
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of perceptions, sources and uses of water among six African communities in the North West Province of South Africa

Abstract: The aim of this study was to assess perceptions, sources and uses of water among African residents of six different impoverished communities in the North West Province (NWP) of South Africa. A sequential exploratory mixed-methods design was used. Twenty-five purposively selected community members took part in the qualitative phase of the study, and during the quantitative phase a sample of 1 000 participants was proportionately and systematically selected from the six communities. The qualitative results were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
2
5
1
Order By: Relevance
“…This is supported by SDM (2020), which report that 75% of the households use standpipes in their dwellings or communal standpipes within 200 m from the households. Majuru et al (2012) and Coetzee et al (2016) found similar results in studies conducted in rural municipalities of South Africa, where most of the households walked not more than 200 m to access improved water services. This was beneficial to the households because literature indicates that children living in households that accessed safe water not more than 500 m from their households were 34% less likely to get infected by water-related diseases (e.g.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This is supported by SDM (2020), which report that 75% of the households use standpipes in their dwellings or communal standpipes within 200 m from the households. Majuru et al (2012) and Coetzee et al (2016) found similar results in studies conducted in rural municipalities of South Africa, where most of the households walked not more than 200 m to access improved water services. This was beneficial to the households because literature indicates that children living in households that accessed safe water not more than 500 m from their households were 34% less likely to get infected by water-related diseases (e.g.…”
Section: Discussionsupporting
confidence: 73%
“…When asked, households were not aware of any water quality issues arising from using improved water services that resulted in an outbreak of any waterborne diseases or mortality. The results concur with those of a study conducted in the rural municipalities of South Africa that found that most participants perceived water to be 'good' based on organoleptic properties as a measure of water quality (Coetzee et al 2016). This is contradictory to the findings of a study conducted by Steelman et al (2015), which found that more than half a the respondents perceived water not to be safe.…”
Section: Water Quality Cost and Use Of Alternative Water Sourcessupporting
confidence: 76%
“…Water storage has been regarded by six African communities in the northwest province of South Africa as a widely recognized method of keeping water quality. 21 Understanding the contamination of the water source is notable because it facilitates the selection of good quality water sources for drinking water supply and offers a basis for establishing treatment requirements within the WHO standard limits. 19 This study attempted to explore participants' knowledge of water quality from protected sources.…”
Section: Discussionmentioning
confidence: 99%
“…The study was used descriptive research with specifically cross sectional survey using designed Questionnaires of community perception on Drinking water quality added interpretation to local Somali language, to make easily understandable; then distributed to all respondents. The Questionnaires was evoked but some of them were taken Hendri Coetzee et al 2016 [5].…”
Section: Methodsmentioning
confidence: 99%
“…Mostly the perception is different form community to community, Hendri Coetzee et al (2016), they revealed that most residents understood the quality of water to relate to aspects like the clarity and colour (cleanliness and brightness), as well as smell and composition and also they found Participants were requested to rate the quality of the water in their communities [5]. The majority (72.4%) regarded the water quality in their area as "average", with a smaller group (24.9%) perceiving their water as being of "good quality".…”
Section: Perception Of Drinking Watermentioning
confidence: 99%